SPAD INDEX IN TOMATOES PLANTS CULTIVATED IN COCONUT FIBER AND SUBMITTED TO FERTIRRIGATION PULSES - Nogueira, B. B.; Iglesias, L.; Mesquita, J. V.; Nakatani, M. C.; Putti, F. F. (Revista Brasileira de Engenharia de Biossistemas, 2018)
Tomato is one of the main vegetables produced in Brazil, adapting to practically all climates, but is susceptible to several diseases that lead to reduced productivity and quality. One of the most important segments in the Brazilian market is table tomatoes, the ’BRS Imigrante’, which tolerates some diseases that cause losses to the producer, falls into this category. Chlorophyll is present in all plants and is one of the factors related to the photosynthetic efficiency of plants and as a consequence of their growth, development and adaptation to diverse environments. Considering the importance of chlorophyll, the objective of this work was to analyze the SPAD A, B and total indices and to investigate their behavior throughout the development of the cultivar. Chlorophyll A, B and total contents were determined in ten evaluation dates after transplanting. The SPAD indices analyzed showed positive correlations between them.